Hydrogeochemical Characteristics of the Haiyuan-Liupanshan Seismic Belt at the Northeastern Edge of the Tibet Plateau - Xinyan Li; Xiaopeng Liu; Jianguo Du; Yueju Cui; Fengxia Sun (Geofluids)
The hydrogeochemical characteristics and groundwater recharge environments along the deep-cut Haiyuan-Liupanshan fault zone (HLFZ) were investigated by major ion and isotopic compositions (δ18O and δD) of the water samples collected at 14 sites from 2016 to 2017. The Schukalev classification method, fuzzy membership function, the proportion coefficients of major ions and principal component analysis (PCA) were adopted to analysis the hydrogeochemistry, water quality, origins and controlling factors of groundwater. In terms of chemical types, the sites along HLFZ can be divided into two groups. Specifically, the Group 1 is in the north and west part of the HLFZ and the water samples are characterized by higher salinity and enriched in Na+ and SO42-, reflecting the control of evaporate dissolution in cretaceous and tertiary aquifers, reverse ionic exchange, stronger water-rock reaction and deep fluids. The higher concentrations of Ca2+ + Mg2+ and HCO3- were found in Group 2, which is located in the southeast of the HLFZ and may be attributed to carbonate weathering and the recharge of karst fissure water from ordovician dolomite and limestone. Contamination of groundwater in HLFZ is severe, with 78.6% of the sites classified as grade V, which means they cannot be used for drinking water or agriculture. The primary contaminants found in Group 1 are TDS, Na+, Cl- and SO42- and the exceedance in NO3-and pH value affect water quality in the Group 2. The 18O and δD values of groundwater in HLFZ indicated that meteoric water contributed dominantly to the groundwater and it was influenced by the water cycle and water-rock reaction. Furthermore, tectonic movement, seismicity, and the level of deformation along different segments of HLFZ are important factors in the migration of deep to shallow groundwater, and water-rock reactions during groundwater migration, which results in differences in chemical composition of the groundwater between Group 1 and Group 2. Most of the sites with higher TDS in HLFZ fall on the a higher stress state region (represented by a low b value<0.75), which reflected a possible evidence of seismic activity affected the hydrogeochemistry of groundwater.